Exiled and Broken: New Amendments to UK’s Discriminatory Immigration Rules Make “Homemaking” Impossible for UK Women - Paloma Allegra Kennedy (Washington University Global Studies Law Review, 2015)
In 2013, the United Kingdom (UK) amended its Immigration Rules to include a myriad of requirements including an increased minimum income that UK citizens must now meet in order to sponsor a spouse who is not a citizen of a European Economic Area. Through these amendments, the UK seeks to prevent and greatly diminish the number of illegal immigrants entering the UK each year. This Note illustrates how the recent amendments prevent UK citizens from reuniting with family in their home country and reinforces persistent gender-specific occupational barriers such as the gender pay gap. It further reveals the amendments effectively exile stay-at-home mothers through a minimum income requirement that must be met first while she is abroad, and again when she returns to the UK. This Note provides suggestions that would allow families to move back to the UK while also promoting the UK’s long-term goal to curb illegal immigration.
Keywords: human rights; citizenship; visa; sponsorship; United Kingdom